2011
DOI: 10.1111/j.1365-2443.2011.01497.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear accumulation of Calcineurin B Homologous Protein 2 (CHP2) results in enhanced proliferation of tumor cells

Abstract: The interaction between calcineurin B homologous protein 2 (CHP2) and Na + ⁄ H + exchanger 1 (NHE1), two membrane proteins, is essential for protecting cells from serum deprivationinduced death. Although four putative EF-hands in CHP2 had been predicted for years, Ca 2+ -binding activities of these motifs have not been tested yet, their role in this process remain poorly understood. To identify Ca 2+ -binding motifs required for the stable formation of CHP2 ⁄ NHE1 complexes, we developed a mutagenesis-based as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…1A and 2), while CHP2 has only NES-1, with CHP3 not having any canonical NES signal. Simultaneous mutations in both NES-1 and NES-2 lead to nuclear localization of CHP1 (94), indicating that one NES is sufficient to transport CHP1 from the nucleus to the cytosol (71).…”
mentioning
confidence: 99%
“…1A and 2), while CHP2 has only NES-1, with CHP3 not having any canonical NES signal. Simultaneous mutations in both NES-1 and NES-2 lead to nuclear localization of CHP1 (94), indicating that one NES is sufficient to transport CHP1 from the nucleus to the cytosol (71).…”
mentioning
confidence: 99%
“…1B), where CHP1 is thought to be important for NHE1 activity and its stabilization and localization to the plasma membrane (9). CHP2 is highly expressed in tumor cells; it is protective against serum deprivation-induced cell death by increasing pH i (10) and may play a role in the enhanced proliferation of tumor cells (11). CHP3, or tescalin (binding site uncertain), is thought to promote maturation and cell surface stability of NHE1 (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical studies have identified an array of CHP binding partners including microtubules, glyceraldehyde, kinesin-related motor KIF1B␤2, calcineurin, the DRAK2 protein kinases, and upstream binding factor (3,23,25,34,40). Studies designed to explore the significance of these biochemical interactions have found that CHPs can regulate calcineurin's phosphatase activity, constitutive vesicle secretion, cytoskeletal organization, proliferation, and cancer metastasis (5,17,26,27,29,49,62).…”
Section: Discussionmentioning
confidence: 97%
“…NHE activity is implicated broadly in the maintenance of cell volume, electrolyte transport, and cytoplasmic pH levels (10,33,57). More specialized functions of sodium-proton exchangers have been noted in particular cell lines, including contributions to cell migration, morphology, proliferation, apoptosis, and tumor metastasis (11,15,16,24,27,36,49,(52)(53)(54)63). The striking multiplicity of reported NHE functions suggests that these proteins may act in a highly context-dependent manner.…”
mentioning
confidence: 97%